Evidence for Arrhythmogenic Effects of A2A-Adenosine Receptors - Peter Boknik; Katharina Drzewiecki; John Eskandar; Ulrich Gergs; Britt Hofmann; Hendrik Treede; Stephanie Grote-Wessels; Larissa Fabritz; Larissa Fabritz; Paulus Kirchhof; Paulus Kirchhof; Paulus Kirchhof; et al. (Frontiers Media S.A., 2019)
Adenosine can be released from the heart and may stimulate four different cardiac adenosine receptors. A receptor subtype that couples to the generation of cyclic adenosine monophosphate (cAMP) is the A2A-adenosine receptor (A2A-AR). To better understand its role in cardiac function, we studied mechanical and electrophysiological effects in transgenic mice that overexpress the human A2A-AR in cardiomyocytes (A2A-TG). We used isolated preparations from the left atrium, the right atrium, isolated perfused hearts with surface electrocardiogram (ECG) recording, and surface body ECG recordings of living mice. The hypothesized arrhythmogenic effects of transgenicity per se and A2A-AR stimulation were studied. We noted an increase in the incidence of supraventricular and ventricular arrhythmias under these conditions in A2A-TG. Moreover, we noted that the A2A-AR agonist CGS 21680 exerted positive inotropic effect in isolated human electrically driven (1 Hz) right atrial trabeculae carneae. We conclude that A2A-ARs are functional not only in A2A-TG but also in isolated human atrial preparations. A2A-ARs in A2A-TG per se and their stimulation can lead to cardiac arrhythmias not only in isolated cardiac preparations from A2A-TG but also in living A2A-TG.